Business and Marketing Strategy of Carlsberg Group Ukraine - Lugovska, Veronika (2014)
Ukraine is a quite new country, which pass through stages of its development. The economic situation is quite unsustainable, because of historical, political, financial, production and cultural issues. Establishing and development of company that proclaimed European principles of business operation can be a challenging opportunity. The case of Carlsberg Group is known as successful entering to the Ukrainian beer market, which gives the possibility to analyze and understand main specifics, goals and consequences of selected marketing and business strategy